N.M.R. below 1 K with a S.Q.U.I.D. magnetometer. - O'Connell, M. D. (University of Ottawa (Canada), 1977)
A SQUID magnetometer has been used to study the N.M.R. signal and the relaxation time of normal aluminum in low magnetic fields as a function of temperature for the purpose of doing thermometry below 1K. The variation of signal amplitude with temperatures and r.f. power is found to agree with the predictions from the Bloch equations. A description is given of the cryostat that used a circulating helium gas heat exchanger to cool the experimental stage to 1.3K and adiabatic demagnetization of a paramagnetic salt to further cool the stage to 240 mK. The N.M.R. spectrum of lithium in a crystal of lithium niobate was also studied at 4.2K. The quadrupole coupling constant e2qQ/h was measured to be 52 +/- 1 KHz and is compared to previous results. The design of a new cryostat to operate below 100 mK to replace the current one in use is discussed. The construction and operation of a liquid helium level indicator is discussed and commented on.
Keywords: Physics, Condensed Matter.